Travel Industry Economics : A Guide for Financial Analysis / [electronic resource] - Vogel, Harold L. (Cambridge : Cambridge University Press, 2012)
Each year, people around the world spend well over one trillion dollars on travel and tourism, making this sector the world's largest, with employment of 300 million people, one-tenth of the global workforce. In this book Harold L. Vogel examines the business economics and investment aspects of major industry components that include airlines, hotels, casinos, amusement and theme parks, and tourism. The result is a concise, up-to-date reference guide for financial analysts, economists, industry executives, legislators, regulators and journalists interested in the economics, financing and marketing of travel-related goods and services. The new edition expands coverage to airport management, Asian gaming, recreational resorts, restaurants, private jet services and advertising. Sections on the pricing and availability of oil and public policy issues such as antitrust and predation have also been added. A glossary, timeline diagrams and technical appendices enhance the book's appeal as a reference tool.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Tourism